Building of Turbiditic Gas Field Dynamic Model with a Simplified 3D Simulation Software - Octria Adi Prasojo; Reza Syahputra (UIR PRESS, 2018)
This study provides a novel approach of building 3D simulation model with extremely shorter time needed using Rubis simulation software from Kappa Engineering. The study focused on X Field that is located in a turbiditic setting, mainly consisted of separated channel bodies filled with gas, located in a slope apron or passive continental margin of Mahakam Delta. Methods of the study is quite contradictive with common reservoir simulation where it includes data integration, data quality control, model geometry building, reservoir properties distribution, and is followed by wells definition to build the 3D simulation model. Afterward, the reliability of the structural model was checked by the volume calculation for each segment from GeoX model where all dynamic and static data used in the simulation were checked using history matching data derived from well-testing. In conclusion, simulation was run and X Field will be producing for 23 years with 3 years and 10 months plateau rate. Where the static and dynamic data are already provided, the simulation conducted here was very beneficial during the exploration phase of a gas field where the whole process of modeling and simulation could be done only for 3 to 6 months.